COVID-19 and Risk of Acute Ischemic Stroke and Acute Lung Injury in Patients With Type II Diabetes Mellitus: The Anti-inflammatory Role of Metformin - Al-kuraishy, Hayder M.; Al-Gareeb, Ali I.; Alblihed, M.; Cruz-Martins, Natália; Batiha, Gaber El-Saber (Frontiers in Medicine, 2021)
Background: Coronavirus disease 19 (COVID-19) is regarded as an independent risk factor for acute ischemic stroke (AIS) due to induction of endothelial dysfunction, coagulopathy, cytokine storm and plaque instability. Method: In this retrospective cohort study, a total of 42 COVID-19 patients with type 2 diabetes mellitus (T2DM) presented with AIS within 1 week of starting COVID-19 signs and symptoms were recruited. According to the current anti-DM pharmacotherapy, patients were divided into 2 groups: Group I: (Metformin group) T2DM patients with COVID-19 and AIS on metformin therapy (850 mg, 3 times daily (n=22), and Group II (Non-metformin group) T2DM patients with COVID-19 and AIS under another anti-DM pharmacotherapy like glibenclamide and pioglitazone (n=20). Anthropometric, biochemical and radiological data were evaluated. Results: Ferritin serum level was lower in metformin-treated patients compared to non-metformin treated patients (365.93±17.41 vs 475.92±22.78 ng/mL, p=0.0001). As well, CRP, LDH and D-dimer serum levels were lowered in metformin-treated patients compared to non-metformin treated patients (p=0.0001). In addition, lung CT scan score of COVID-19 patients was 30.62±10.64 for metformin and 36.31±5.03 for non-metformin treated patients. Conclusion: Metformin therapy in T2DM patients was linked to a lower risk of AIS during COVID-19. Further studies are needed to observe the link between AIS in COVID-19 diabetic patients and metformin therapy.